A Crisis of Crisis Management? Evaluating Post-2010 Housing Restructuring in Nanjing, China. Issue 1 (2nd January 2018) - Zhang, Zhao; Moore-Cherry, Niamh; Redmond, Declan
Abstract: In less than 20 years the housing system in China has been transformed from one based predominantly on the public provision of housing to a market-based system, to the extent that more than 80% of households in urban China are homeowners. The sheer scale of this change, compressed into such a short time, is impressive. However, the move to a commodified system has not been problem free. Indeed, the twin issues of displacement and, more generally, affordability are coming increasingly to the fore, resulting in significant policy shifts since 2010 toward the promotion of low-end housing for lower middle- and low-income groups. This article examines these issues through a detailed analysis of the implementation of the indemnificatory housing policy in Nanjing, and highlights the complex and often contradictory nature of this policy in practice.